Growth rate, leaf area index and productivity of jambu grown in a hydroponic system - Cunha, Hudson Pierre da Silva; Casais, Luana Keslley Nascimento; Alves Dos Santos, Núbia de Fátima; Ruffeil Alves, Gustavo Antonio; Da Silva Melo, Márcio Roberto; da Silva Borges, Luciana (Comunicata Scientiae, 2022)
The jambu (Spilanthes oleracea L.) is a leafy vegetable with medicinal characteristics, where it is used for various purposes, whether food, cosmetics or medicinal. The work aimed to carry out the growth analysis in jambu plants, grown in hydroponic system. The experiments were conducted at the company B&A Hidroponia, in a hydroponic cultivation system NFT, in a protected environment. The experimental design used was completely randomized with six treatments and three replications. Morphophysiological indices, culture growth rate, relative growth rate, net assimilation rate and productivity were analyzed. Crecism analysis showed that the jambu plant in a hydroponic system has higher morphophysiological indexes after the 39-day cycle and was directly influenced by the liquid assimilation rate (TAL), which is influenced by the duration of the leaf area (DAF), the producer must pay attention to the handling of the nutrient solution. And a productivity of 11.39 Kg / m2 at 54 DAS of cultivation in hydroponics.